Prospective Comparison of Hypofractionated Versus Normofractionated Intensity-Modulated Radiotherapy in Breast Cancer: Late Toxicity Results of the Non-Inferiority KOSIMA Trial (ARO2010-3) - Sarria, Gustavo R.; Welzel, Grit; Polednik, Martin; Wenz, Frederik; Abo-Madyan, Yasser (Frontiers in Oncology, 2022)
Purpose To compare the late toxicity profile of hypofractionation and normofractionation for whole-breast radiotherapy in breast cancer (BC) patients after conserving surgery. Methods Sixty-year old or older patients with pTis-pT3, pN0-pN1a, M0 BC were recruited and stratified to hypofractionated (arm R-HF) or normofractionated (arm L-NF) intensity-modulated radiotherapy (IMRT), for right- and left-sided BC, respectively, in this single-center, non-randomized, non-inferiority trial. A boost was allowed, if indicated. The primary outcome was the cumulative percentage of patients developing grade III fibrosis, grade I telangiectasia and/or grade II hyperpigmentation after 2 years, with a pre-specified non-inferiority margin of 15% increase from an expected 2-year toxicity rate of 20%. Results Median follow-up was 4.93 (0.57–8.65) years for R-HF and 5.02 (0.65–8.72) years for L-NF (p=0.236). Median age was 68 (60–83 and 60–80) years, respectively. In total, 226 patients were recruited (107 for R-HF and 119 for L-NF), with 100 and 117 patients suitable for assessment. A boost was delivered in 51% and 53% of each arm. Median PTV volumes were 1013.6 (273–2805) cm3 (R-HF) and 1058.28 (315–2709) cm3 (L-NF, p=0.591). The 2-year primary endpoint rate was 6.1% (95% CI 1.3-11.7, n=5 of 82) and 13.3% (95% CI 7-20.2, n=14 of 105), respectively (absolute difference -7.2%, one-sided 95% CI ∞ to -0.26, favoring R-HF). No local recurrence-free- or overall-survival differences were found. Conclusion Hypofractionation is not inferior to normofractionated whole-breast IMRT, regarding toxicity. These data further support establishing hypofractionation as the standard of care for BC treatment.